Posttraumatic Stress and Somatic Symptoms in Firefighters: A Mediation Analysis of the Impact of Potentially Traumatic Events - Becker, Joana Proença (2023)
Firefighters are considered a high-risk group for developing stress-related psychopathologies, such as post-traumatic stress disorder (PTSD), due to repeated exposure to potentially traumatic events (PTE). Studies have indicated that PTE is also associated with the development of Somatic Symptom Disorder (SSD). However, the occurrence of this condition among firefighters is an underexplored topic. This study aimed to assess the relationships between PTE and PTSD symptoms, and the relationship between PTE and SSD symptoms. Furthermore, we aimed to assess the role of SSD in the relationship between PTE and PTSD within Portuguese firefighters who battled the 2017 violent forest fires. To this end, a sample of 116 firefighters (75% male) completed self-report measures of posttraumatic symptoms, somatic symptoms, and other psychopathological symptoms. Contrary to several literature, in the present study, neither PTSD nor SSD symptoms seem to be correlated with any sociodemographic characteristics. However, the exposure to PTE is positively correlated with both PTSD and SSD symptoms. Furthermore, SSD seems to act as a mediator in the relationship between PTE and PTSD.